An Epigenetics‐Inspired DNA‐Based Data Storage System. Issue 37 (21st July 2016) - Mayer, Clemens; McInroy, Gordon R.; Murat, Pierre; Van Delft, Pieter; Balasubramanian, Shankar
Abstract: Biopolymers are an attractive alternative to store and circulate information. DNA, for example, combines remarkable longevity with high data storage densities and has been demonstrated as a means for preserving digital information. Inspired by the dynamic, biological regulation of (epi)genetic information, we herein present how binary data can undergo controlled changes when encoded in synthetic DNA strands. By exploiting differential kinetics of hydrolytic deamination reactions of cytosine and its naturally occurring derivatives, we demonstrate how multiple layers of information can be stored in a single DNA template. Moreover, we show that controlled redox reactions allow for interconversion of these DNA‐encoded layers of information. Overall, such interlacing of multiple messages on synthetic DNA libraries showcases the potential of chemical reactions to manipulate digital information on (bio)polymers. Abstract : Information storage : Inspired by the epigenetic regulation of genomic information in cells, it is shown how digital data can undergo controlled changes when encoded in synthetic DNA strands. Chemical transformations were used to alter naturally occurring cytosine derivatives, which enabled the reversible recovery of multiple data layers from a single DNA template (see portraits).